Trastuzumab in Human Epidermal Growth Factor Receptor 2‐Positive Early Breast Cancer: Results of a Prospective, Noninterventional Study on Routine Treatment Between 2006 and 2012 in Germany. (February 2017) - Dall, Peter; Koch, Thorsten; Göhler, Thomas; Selbach, Johannes; Ammon, Andreas; Eggert, Jochen; Gazawi, Nidal; Rezek, Daniela; Wischnik, Arthur; Hielscher, Carsten; Keitel, Stella; Cirrincione, Ursula; et al.
Abstract: Purpose: Trastuzumab is part of the standard treatment in patients with human epidermal growth factor receptor 2‐positive early breast cancer in addition to (neo)adjuvant chemotherapy. This German prospective noninterventional study, which included major patient cohorts underrepresented in the pivotal randomized studies, examined the generalizability of the results of those studies. Patients and Methods: Between 2006 and 2012, 4, 027 patients were enrolled and treated with trastuzumab; they were unselected regarding age or concomitant/sequential adjuvant chemotherapy. Long‐term outcome data were obtained in yearly intervals. All analyses were descriptive in nature. Results: Among 3, 940 evaluable patients, 26% were elderly (older than 65 years of age). More than half of the population had pN0 tumor stage. Ninety‐four percent received chemotherapy: 78% as adjuvant treatment and 14% as neoadjuvant treatment, 2% both. Anthracyclines were administered in 87% and taxanes in 66%. Trastuzumab was stopped prematurely in 9% (because of cardiotoxicity in 3.5%). Recurrence‐free survival was 90.0% (95% confidence interval [CI], 88.9%–91.1%) and 82.8% (95% CI, 81.2%–84.4%) after 3 and 5 years, respectively. The corresponding figures for overall survival were 96.8% (95% CI, 96.1%–97.6%) and 90.0% (95% CI, 88.6%–91.4%). Pathological primary tumor size, lymph node involvement, and hormone receptor status had the greatest independent effect on recurrence risk. Cardiac function toxicity of National Cancer Institute common toxicity criteria grade ≥2 and ≥3 was observed in 2.5% and less than 1% of patients, respectively. Conclusion: The maturing follow‐up data seem to confirm the beneficial results of trastuzumab treatment for early breast cancer from the randomized studies. Moreover, these findings support use of trastuzumab‐based therapy in patients groups less commonly included in the phase III trials (e.g., elderly patients and those with stage I disease). Implications for Practice: On the basis of the results of large pivotal phase III studies, the inclusion of trastuzumab in adjuvant treatment regimens for human epidermal growth factor receptor 2‐positive breast cancer is standard of care. However, in these trials, elderly patients, those with comorbidities, and/or those with contraindications or refusal of cytotoxic chemotherapy are typically underrepresented. This study provides data on observed treatment options, outcomes, and risks in a wider, unselected patient population (including more than 1, 000 patients with stage I disease), treated routinely in several institutions of varying size and location across Germany. Abstract : Maturing follow‐up data from this study seem to confirm the beneficial results of trastuzumab treatment for early breast cancer from previous randomized studies. Moreover, these findings support use of trastuzumab‐based therapy in patients groups less commonly included in the phase III trials (e.g., elderly patients and those with stage I disease).